Demonstration of infectious bovine rhinotracheitis (IBR) virus antigens by immunoperoxidase staining - Bulut, Hakan; Bolat, Yusuf; Özdarendeli, Aykut; Doymaz, Mehmet Z.; Gürhan, S. Ismet (My University, 1998)
In this study, cellular localization of IBR-IPV (Infectious Bovine Rhinotracheitis-Infectious Pustular Vulvovaginitis) virus antigens at various times of infection was studied. For this purpose, MDBK cells wre infected with IBR-Colorado strain and cellular distribution of viral antigens were followed at early and late periods of infetction. Immunohistochemical staining of virus antigens were performed by using IBR-Colorado immune Balb/C mouse serum and horse radish peroxidase-conjugated goat anti-mouse immunoglobins as primary and secondary antibodies, respectively. Until the third hour of infection, viral antigens were confined to the nucleus of infected cells, however, at later times, viral antigens were distributed to both nucleus and cytoplasm. As the time period of infection increased, the amount of viral antifens detected became abundant. At those period, typical cytopathic changes of IBR-IPV infection such as swelling of the cells and distention of cytoplasm were noticed in infected cells.
Infectious Bovine Rhinotracheitis (IBR) Virus Antijenlerinin Lokalizasyonunun Immunoperoksidaz Boyama ile Gösterimi
Keywords: ELISA; IBR; Immunoperoxidase